Maqsūdī and The Importance of His Work Named Istiftāh in Perspective of Arabic - İsmail Ekinci (Şarkiyat Mecmuası)
This study describes Maqsūdī and the importance of his work Istiftāh in perspective of the Arabic language. First, Maqsūdī’s life, his scientific and educational personality, and works are described. The author’s Istiftāh is discussed in detail and the topics covered in the work are revealed. Finally, the importance of Maqsūdī and his work Istiftāh in perspective of Arabic are discussed. The science that reveals the grammatical principles of Arabic is called grammar, and the science that examines the morphological structures of words is called morphology. Hundreds of language scholars have grown from the first period to this day, teaching people the rules of Arabic grammar and morphology.These scholars wrote hundreds of works on grammar and morphology, and these works were often used as textbooks. Ahmad Hādi Maqsūdī (1868-1941) was a language educator who devoted his life to Arabic education and wrote many works on grammar and spelling in Crimean Turkish. Maqsūdī was an important scholar in teaching Arabic, attracting attention primarily through his work as a professor, the textbooks he prepared, and the teaching methods he developed in these books. Especially his Istiftāh is an important work for Arabic. Istiftâh, which is an Arabic morphology book prepared for students studying in secondary schools and madrasas, presents the subjects in a very systematic way, and the subjects in the work are ordered in a way to facilitate learning in stages.